Effect of Preoperative Chemotherapy in the Treatment of Advanced Wilms Tumor (Journal of Paediatric Surgeons of Bangladesh, 2015)
Introduction: The management of Wilms tumor still remains a matter of great challenge to pediatric surgeons and also to pediatric oncologists. The tumor continues to be the subject of intensive investigations that with the aid of co-operative protocols by the National Wilms Tumor Study (NWTS) have resulted in marked improvement in survival. Surgical excision remains the cornerstone of treatment of Wilms tumor; however the dramatic improvement in overall survival is the result of coordinated use of surgery, chemotherapy and radiation therapy.Materials and methods: This was a prospective study, started in September, 1999 and completed in November, 2000 in Pediatric Surgery department of Dhaka Shishu (Children) Hospital and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Preoperative chemotherapy was given to all the patients of advanced Wilms tumor for four weeks with vincristine and actinomycin D according to the Societe Internationale d Oncologie Pediatrique (SIOP) protocol (Herdrich K, 1982). The patients were followed up every 2 weekly by ultrasonography, LFT, Hb% and chest X-ray for one month. The size of the tumor as well as the metastatic lesions in the prechemotherapeutic and postchemotherapeutic ultrasonographic findings was compared after one month.Results: After giving neoadjuvant chemotherapy, the size of the tumor was reduced in 08 patients and it was measured by USG after one month. The change in the metastatic lesions was also compared by USG at the same time. Two patients died during the course of neoadjuvant chemotherapy and nephroureterectomy was done in 08 patients. All the resected specimens were sent for histopathology. The reports revealed features of Wilms tumor with favorable histology (FH) in 07 cases and unfavorable histology (UH) in 01 case.Conclusion: It is evident from this study that advanced stage of Wilms tumor, where operative treatment was not primarily possible, preoperative chemotherapy downsized the tumor significantly. It is then possible to perform nephroureterectomy.J. Paediatr. Surg. Bangladesh 3(2): 56-60, 2012 (July)